2018
DOI: 10.1016/j.juro.2018.04.082
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Cancer Survival of Men Receiving 5α-Reductase Inhibitors

Abstract: Patients who receive 5α-reductase inhibitors have improved disease specific survival after bladder cancer diagnosis compared to those who do not receive them while α-blockers were not associated with survival. This supports the benefits of 5α-reductase inhibitors in bladder cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 8 publications
2
17
0
Order By: Relevance
“…Kaplan-Meier analysis of recurrence-free survival with and without 5-ARI stratified by amount of BCG received: (A) Group I < 6 instillations (B) Group II < 1 year maintenance (C) Group III at least 1 year maintenance. who received 5-ARIs had a 25% reduction in disease specific survival compared to the control group who received ␣-blockers [12]. Finally, an evaluation of AR expression in bladder tumors from patients who also received androgen deprivation therapy suggests that these beneficial effects may be due to an AR-mediated effect of the loss of androgens [14].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Kaplan-Meier analysis of recurrence-free survival with and without 5-ARI stratified by amount of BCG received: (A) Group I < 6 instillations (B) Group II < 1 year maintenance (C) Group III at least 1 year maintenance. who received 5-ARIs had a 25% reduction in disease specific survival compared to the control group who received ␣-blockers [12]. Finally, an evaluation of AR expression in bladder tumors from patients who also received androgen deprivation therapy suggests that these beneficial effects may be due to an AR-mediated effect of the loss of androgens [14].…”
Section: Discussionmentioning
confidence: 95%
“…In preclinical models the androgen receptor (AR) has been implicated in the development and progression of bladder cancer [6,7,11]. More recently, several clinical studies have suggested that men who receive 5-ARIs may have better bladder cancer outcomes [8,9,12,13]. Shiota et al demonstrated a reduced bladder cancer recurrence rates among patients who received 5-ARIs or androgen deprivation therapy in a cohort of 228 Japanese men [8].…”
Section: Discussionmentioning
confidence: 99%
“…However, a study conducted by Ville et al has compared the bladder cancer specific mortality rate between 5-ARIs and α-blockers, a drug group that may also be affected by the same lead time bias with different medication mechanism. The risk reduction was only discovered in the 5-ARIs group, which indicated that lead time bias could not fully explain the decreased mortality rate [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…# P < 0.05 (vs. testosterone treatment).up demonstrated a significantly lower incidence of bladder cancer in men with finasteride treatment (1.07%) than in those without 5␣-RIs (1.46%) (hazard ratio 0.634; P = 0.0004)[18]. The beneficial effects of 5␣-RI therapy on the development and/or progression of bladder cancer have been further supported by a meta-analysis of 5 studies[30] as well as subsequent retrospective studies[20][21][22]. However, data from a double-blinded randomized clinical trial to determine if an ␣1-blocker doxazosin and/or finasteride could prevent the progression of BPH indicated no impact of 5␣-RI therapy (P = 0.67) on bladder cancer incidence in men with [9/1,216 (0.74%)] versus without [9/1,484 (0.61%)] finasteride treatment[19].…”
mentioning
confidence: 87%